PERAN AKUNTANSI DALAM PROSES REFORMASI BIROKRASI : STUDI KASUS PADA UNIT KERJA KEMENDIKNAS Haryani & M. Syafruddin - haryani - (LPPM STIE DHARMAPUTRA SEMARANG, 2012)
Abstract The objective of this research is to explore the role of accounting in the reform process of a continuously evolving govermental agency in one of sub units in ministary of national education. It is important that essentially birocratic reforms still in progress.Drawing on two complementary organizational change models, the paper investigates how the shifting objectives of Unit Kerja of National Education Department rendered its financial management and accountability systems inadequate and how new accounting technologies introduced to anchor the reform process clashed with bureaucratic procedures to create a very challanging context for the organization’s management. The paper uses multiple research methods including inteviews, archival material and observation to understand the reform process at one of Unit Kerja of National Education Department and its implication for public sector accounting and public sector managemnet.The paper finds that the unique history and continuously evolving nature of Unit Kerja of National Education Department make it an important context for re-examining the dynamics of change process and the contribution of accounting technologies within that context. Since the late 2001, the Unit Kerja of National Education Department has transformed itself from the budget system was established by top down system called centralized budget system to participative budgeting called decentralized budget system. Keywords: Peran Akuntansi, Proses Reformasi Birokrasi